2020
DOI: 10.1037/dev0000900
|View full text |Cite
|
Sign up to set email alerts
|

Preschool language ability is predicted by toddler hand preference trajectories.

Abstract: Prior work has found links between consistency in toddler handedness for the fine motor skill roledifferentiated bimanual manipulation (RDBM), and language development at 2 and 3 years of age. The current study investigated whether consistency in handedness from 18 to 24 months (N ϭ 90) for RDBM predicts receptive and expressive language abilities assessed using the Preschool Language Scales 5th edition (PLS-5) at 5 years old. Latent class growth analyses identified 3 stable RDBM hand preference trajectories: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 76 publications
1
32
0
Order By: Relevance
“…Thus, some children exhibit consistent hand-use preferences from infancy, whereas others are variable. Consistency in the trajectory of hand-use preference matters because handedness trajectories for later-emerging RDBM skill predict language outcomes when children are 2, 3, and 5 years old (Gonzalez et al, 2020). Moreover, this link to language outcomes extends the cascade theory further in developmental time, past the emergence of a hand-use preference in RDBM tasks.…”
Section: Developmental Insights Into Handednessmentioning
confidence: 99%
“…Thus, some children exhibit consistent hand-use preferences from infancy, whereas others are variable. Consistency in the trajectory of hand-use preference matters because handedness trajectories for later-emerging RDBM skill predict language outcomes when children are 2, 3, and 5 years old (Gonzalez et al, 2020). Moreover, this link to language outcomes extends the cascade theory further in developmental time, past the emergence of a hand-use preference in RDBM tasks.…”
Section: Developmental Insights Into Handednessmentioning
confidence: 99%
“…In addition, toddlers who had the strongest and most consistent righthand-use preference from 18 to 24 months had higher expressive and receptive language scores at three years of age (measured with Preschool Language Scales, 5th edition) than toddlers with a left-hand-use preference or with a weak right-hand-use preference [284]. By five years of age, children, who as toddlers, had a strong right-hand-use preference, scored significantly higher on both expressive and receptive language skills (PLS-5) compared to those with a left-hand-use preference or a weak right-hand-use preference [285]. Thus, individual differences in fine motor skills (RDBM) during toddlerhood can have cascading effects on language ability during the preschool years.…”
Section: Significance Of Handedness For Hemispheric Specialization and Coordinationmentioning
confidence: 99%
“…While the scope of this specific study focuses on children who are already speaking, an additional benefit of developing a motor intervention is that it could be applied to children who are nonverbal. The previously cited studies linking increased right-hand use and later proficient language development (Gonzalez et al, 2020;Nelson et al, 2017) suggests this could provide a very effective training tool.…”
Section: Discussionmentioning
confidence: 97%
“…Children who demonstrated inconsistent selection of a hand for writing were more likely to have poor vocabulary skills (Crow et al., 1998). A recent longitudinal study found that consistently higher right‐hand use for object manipulation during a role‐differentiated bimanual task in infancy predicted better language skills (expressive and receptive) at 5 years of age (Gonzalez et al., 2020). These two studies suggest that the relationship between lateralized motor actions and vocabulary persists throughout childhood, but clearly more research is needed to firmly establish this link.…”
Section: Introductionmentioning
confidence: 99%